Visualization of Hashtag War in digital activism spontaneous on social media - Firna Sayyidatul Qurroh 'Aini; Nur'annafi Farni Syam Maella; Zulaikha Zulaikha (Universitas Ahmad Dahlan, 2025)
This study explores visualization patterns in Indonesia’s spontaneous digital activism through three major hashtags, #KaburAjaDulu, #ResetIndonesia, and #fyp, using Norman Fairclough’s Critical Discourse Analysis (CDA). A total of 300 social media posts from Twitter (X), Instagram, and TikTok were purposively selected and analyzed at three levels: textual, discursive, and social practice. The results reveal that each hashtag demonstrates distinct visual and narrative strategies shaped by the issue context, participating actors, and distribution mechanisms. #KaburAjaDulu reflects spontaneous satire and public frustration through memes and videos, #ResetIndonesia articulates reformist discourse via structured visuals such as infographics and digital posters, while #fyp functions as an algorithmic amplification strategy on TikTok. These visualizations construct dominant and counter-narratives that reflect broader socio-political tensions and digital resistance. The study contributes to digital political communication scholarship by integrating visual discourse analysis with critical theory, offering new insights into how visual symbols and platform algorithms collectively shape public opinion and facilitate collective engagement in Indonesia’s evolving online political sphere.